Governmental and Intergovernmental Immunity in Australia and Canada - McNairn, Colin (Heritage, 2019)
As the state comes to play a larger role in the community the question of the extent to which government is subject to the general law of the land assumes increasing importance. This book examines the limits of two related forms of state immunity: crown or governmental immunity from statue and intergovernmental immunity. The first results from the rule of statutory construction that the crown, representing the executive government, is not bound by legislation except by express words or necessary implication. The second is of a constitutional order and provides a degree of freedom to each level of authority in a federal system from the laws of the other level of authority.The author considers, in separate chapters, the effect which statues can have upon a government when it confronts the legal system in tort proceedings, in criminal actions, as a party to a contract, as a creditor, and as a potential taxpayer. Some of the particular questions that are canvassed are as follows: can the crown recover damages against a subject beyond the limit liability prescribe by statue? Is a servant of the crown, such as a member of the armed forces, liable to conviction for a traffic offence committed while in the course of his duty? Is the Commonwealth of Australia as a landlord limited in what it may charge its tenants by state rent control legislation? Can a provincial liquor board import supplies for resale free of Canadian customs duties? The author's examination of judicial decisions on intergovernmental immunity, one of the most difficult areas of constitutional law, exposes the confusion that exists as to the precise scope of the immunity. One of the principal purposes of this book is to impose some order on his jurisprudential chaos and to suggest directions of approach for the future. This incisive analysis of a crucial area of the law will be interest to all who are concerned with governmental accountability as well as to jurists, judges, and lawyers